An Empirical Study on Consumer Trust in Online Shopping in Punjab - Thakur, Anand; Shabnam; Kaur, Rupinderdeep (Indian Journal of Marketing, 2017)
Online shopping in India is an emerging trend for marketers for promoting their merchandise in a wide geographical area using the Internet. India acquired 283.8 million Internet users by 2016. India is now the third largest Internet user after the U.S. and China. Lack of trust is the biggest obstacle to the success of online shopping. The present study focused upon the relationship of trust antecedents with consumer trust and consumer trust with online shopping activities with the help of a cross-sectional survey conducted in Punjab. Structural equation modeling (SEM) was used to achieve the results of this research. The results revealed that knowledge and privacy protection did not have a significant relationship with consumer trust. The results revealed that security protection, perceived risk, and perceived benefits are very important antecedents for building trust among the consumers towards online shopping. Consumer trust was found to have a significant relationship with online shopping activities. Finally, some useful implications have been offered for the marketers at the end.